Innovative Data Transmission and Routing Strategies of Wireless Body Area Sensor Networks: Taxonomy, Review, Issues and Constraints of State of the Art Contributions in Recent Literature - Anirudh Reddy, R; N.Venkat Ram, Dr (International Journal of Engineering and Technology, 2018)
Wireless body area sensor networks (WBASN) is an effective solution that has proposed in terms of improving the solutions and their varied benefits that have been achieved from the usage of WBASN solutions in communication, healthcare domain. From the review of stats on rising number of wireless devices and solutions that are coming up which is embraced by the people as wearable devices, implants for medical diagnostic solutions, etc. reflect the growing demand for effective models. However, the challenge is about the effective performance of such solutions with optimal efficiency. Due to certain intrinsic factors like numerous standards that are available, and due to the necessity for identifying the best solutions that are based on application requirements. Some of the key issues that have to be considered in the process of WBASN are about the impacts that are taking place from the wireless medium, the lifetime of batteries in the WBASN devices and the other significant condition like the coexistence of the systems among varied other wireless networks that are constituted in the proximity. In this study, scores of models that have propose pertaining to MAC protocols for WBASN solutions have reviewed to understand the efficacy of the existing systems, and a scope for process improvement has explored for conducting in detail research and developing a solution.Â